Evaluation of potentially inappropriate medications for the elderly according to beers, STOPP, START, and Chinese criteria - Zhu, Xiaojuan; Zhang, Feng; Zhao, Yong; Zhang, Wen; Zhang, Yahui; Wang, Jianchun (Frontiers in Pharmacology, 2024)
Objective: Polypharmacy prevalence is increasing worldwide, and it is becoming more popular among the elderly. This study aimed to compare the prevalence of potentially inappropriate medications (PIMs) using the Beers criteria (2019 edition), criteria for potentially inappropriate medications for older adults in China (Chinese criteria), Screening Tool of Older Persons’ Prescriptions (STOPP), and Screening Tool to Alert to Right Treatment (START) criteria and to identify risk factors associated with PIM use. Methods: This was a cross-sectional study with a sample of 276 inpatients aged ≥65 years old from January 2020 to June 2020. A cross-sectional study was conducted to analyze PIMs based on the Beers (2019 edition), Chinese, STOPP, and START criteria. PIMs use was analysed based on four different criteria and logistic regression analysis was used to investigate independent factors associated with PIM use. Results: The mean number of medications used by the elderly population was nine (range, 0–28). A total of 252 patients (accounting for 91.30%) took five or more medications and 120 patients (accounting for 43.48%) took 10 or more medications. The prevalence rates of PIMs were 66.30% (183/276), 55.07% (152/276), 26.45% (73/276), and 64.13% (177/276) determined by the Beers, Chinese, STOPP, and START criteria, respectively. The top PIMs screened using the Beers, Chinese, and STOPP criteria were proton pump inhibitors, clopidogrel, and benzodiazepines, respectively. Missed use of ACEI in patients with systolic heart failure and/or coronary artery disease was found to be the most common potential prescription omission (PPOs) analyzed using the START criteria. Logistic regression analysis showed that the strongest predictor of PIMs, as determined by all four criteria, was an increased number of medications (p < 0.001). Age was another risk factor for PIMs based on the STOPP criteria in our study (p < 0.05). Conclusion: Polypharmacy and PIMs were common in our study, and the risk of PIMs correlated with polypharmacy. Application of the Beers, Chinese, STOPP, and START criteria is a useful tool for detecting PIM use.